Eksplorasi Komprehensif Hukum Keluarga Islam di Indonesia: Sejarah, Prinsip, dan Praktik Kontemporer - Aulil Amri; Fariqan Malhusna; Maryam Thahira; Nissa Azra Nabila; Nabila Miswar; Saniah Amatillah; Ibrahim Adeyemi Adewumi (Yayasan Cendekia Gagayunan Indonesia, 2025)
This paper aims to comprehensively examine Islamic Family Law in Indonesia, focusing on its historical development, legal sources, and core components such as marriage, inheritance, divorce, wills, adoption, and gifts. The method used is a literature review of Islamic legal texts and national regulations, particularly the Compilation of Islamic Law (KHI) and the Marriage Law. The results show that Islamic Family Law in Indonesia has significantly evolved, especially since the enactment of Law No. 1 of 1974 and the implementation of KHI through Presidential Instruction No. 1 of 1991. Nevertheless, challenges remain in terms of implementation, public understanding, and criticism of certain provisions perceived as gender- biased. Ongoing reform and contextualization are needed to ensure Islamic family law delivers more equitable justice in Indonesia’s pluralistic society.